THE ASSOCIATION BETWEEN MATRIX METALLOPROTEINASE-9 (MMP-9) WITH HIGH SENSITIVE TROPONIN T (hs-TnT) IN PATIENT WITH ACUTE MYOCARDIAL INFARCTION - Suyasa, I Putu Gede Eka Ariawan; Rina, Ketut; Widiana, I Gde Raka (Medicina; Vol 46 No 1 (2015): Januari 2015)
Mechanism of acute myocardial infarction (AMI) is previously due to atherosclerotic plaque rupturewith occurs because extra-cellular matrix of plaque fibrous cap destruction or degradation by proteaseenzyme matrix metalloproteinase-9  (MMP-9), which released by macrophage cell.Increased plasmaMMP-9  is  predisposition  factor  of  atherosclerotic  plaque  rupture  in AMI  and  followed  by  acutethrombosis inside coronary artery lumen which caused myocardial ischemic and clinical sign of AMI. Ifthe ischemic process continuous and ongoing that can caused myocardial necrosis which can increasedplasma troponin. High sensitive troponin T (hs-TnT) newly and more sensitive detection of plasmacTn-T  than conventional.The aim of  this study was  to determined  the association between plasmaMMP-9 with hs-TnT in AMI patients.This study was a cross-sectional observational which performedin 62 patients with AMI which enrolled by consecutive sampling at Sanglah Hospital Denpasar fromDecember 2011 until December 2012. MMP-9 and hs-TnT plasma level were measured 48 hours afteronset IMA. Sixty two patients AMI were involved in this study consist of 35 STEMI patients (56.5%)and 27 NSTEMI patients (43.5%), the mean plasma MMP-9 was 23.9 (SD 0.42) ng/mL and hs-TnT was464.7 (SD 39.3) ng/mL.The results of this study were positive correlation between MMP-9 and hs-TnTAMI  patients  (r=  0.507; Y=  -  650.6 +  46.7(X1); P<0.0001);  plasma MMP-9  and  onset  of AMI wereinfluenced to plasma hs-TnT with formulationY = - 815.0 + 46.5(X1)+ 20.7(X2); (â MMP-9=46.5(95%CI: 24.7 to 68.4); P<0.0001; â onset AMI=20.7(95%CI : 2.1 to 39.4); P=0.030) and there was more strongercorrelation betweenMMP-9 and hs-TnT in STEMI group than NSTEMI. [MEDICINA 2015;46:22-27]. Mekanisme terjadinya infark miokard akut (IMA) didahului oleh proses ruptur plak aterosklerosisdan diawali dengan destruksi atau degradasi matriks ekstraseluler fibrus cap plak oleh enzim proteaseyang dihasilkan sel makrofag yaitu matrix metalloproteinase-9 (MMP-9). Kadar MMP-9 yang meningkatmerupakan  faktor  predisposisi  terjadinya  ruptur  plak  aterosklerosis  pada  IMA  yang  diikuti  olehproses  trombosis akut pada  lumen arteri koroner yang menyebabkan proses  iskemia miokard dangejala klinis IMA. Proses  iskemia yang tidak teratasi akan mengakibatkan nekrosis miokard yangditandai meningkatnya troponin jantung. Pemeriksaan high sensitive troponin T (hs-TnT) merupakanpemeriksaan kadar  troponin yang  terbaru dan memiliki kemampuan  lebih baik dari pemeriksaantroponin konvensional. Tujuan dari penelitian ini untuk mengetahui hubungan kadar MMP-9 denganhs-TnT plasma pada penderita  IMA. Penelitian  ini merupakan  studi observasional potong  lintangyang dilakukan pada   62 penderita  IMA yang dikumpulkan  secara  consecutive  sampling di RSUPSanglah Denpasar dari Desember 2011 sampai Desember 2012. Kadar plasma MMP-9 dan hs-TnTdiukur 48  jam  setelah awitan  IMA. Dari 62  sampel penelitian yang  terdiri dari 35 pasien STEMI(56.5%) dan 27 pasien NSTEMI (43.5%) didapatkan rerata kadar MMP-9 plasma 23.9 (SB 0.42) ng/mL dan hs-TnT plasma 464.7  (SB 39.3) ng/mL.Hasil penelitian  ini terdapat korelasi positif antaraARTIKEL ASLI  JURNAL  ILMIAH KEDOKTERAN  • 23death in the world,1 approximately30% from all cause of death.2Acutecoronary syndrome (ACS) is one ofcoronary  heart  diseasemanifestation  and  a  seriouscardiovascular emergency.3Basic  pathogenesis  acutemyocardial  infarction  isatherosclerotic  plaque  rupturewith following thrombus formationin coronary artery. The process ofatherosclerotic plaque rupture iscaused  by  protease  enzymereleased  from macrophage  cell,such as matrix metalloproteinase-9 (MMP-9), that cause degradationand fibrous cap rupture and formthrombus with coagulation cascadeactivation.  This  thrombusformation  will  give  clinicalmanifestation of ACS and increaseof troponin levels.4-7Cardiac  troponin  (cTn),cTnTand  cTnI , is a gold standardfor  detection  of  myocardialnecrosis.5,8 Using high  sensitivecardiac  troponin  (hs-cTn),    hs-TnTand hs-TnI, will improve earlydiagnosis  of  acute myocardialinfarction (AMI) significantly andhopefully  will  decrease  falsepositive result.5,9Several  studies  have  beendone  to  compare MMP-9  levelswith hs-TnT in patients with ACS.Kobayashi  et al10  found MMP-9levels increased in acute phase ofACS  as  reflection  of  plaquevulnerability  and hs-TnT  levelsincreased in later phase. Setiantoet al11 in 2011 compared MMP-9levels MMP-9 and troponin-I (cTn-I)  in  ST Elevation MyocardialInfarction (STEMI) and UnstableAngina Pectoris  (UAP)/ Non STElevation Myocardial Infarction(NSTEMI) with result a positivecorrelation  between  increase  ofMMP-9 levels and cTn-I mainly inSTEMI group and stated MMP-9role in myocardial damage severitywith r=0.33 and P=0.003. Thereis  no  research  that  studycorrelation  between  increase  ofMMP-9 levels and hs-TnT in AMIpatients.METHODSThis  study  was  aobservational  study with  cross-sectional design to evaluate MMP-9 levels and hs-TnT levels in AMIpatients at  emergency unit andIntensive  Cardiac  Care Unit(ICCU) Cardiology DepartementUdayana University MedicalSchool/ Sanglah Hospital. Thisstudy was a research tree aboutACS  that  has  been  held  fromDecember  2011 until December2012 and the result became JointStudy of ACS. This study has beenapproved by Ethics Committee ofUdayana University MedicalSchool/Sanglah  HospitalDenpasar. Subjects of this studywere 62 patients with AMI thatfulfilled  inclusion and exclusioncriteria. The  inclusion  criteriawere: 1) all AMI patients age 30-80  years  old  and  treated  atemergency unit and ICCU SanglahHospital,  2)  gave  consent  toparticipate  in  this  study.  Theexclusion criteria were : 1) valvularheart diseases (VHD), 2) congestiveheart  failure  (CHF), 3) acute orchronic  liver disease, 4)  chronickidney disease (CKD) (creatinineclearance < 60 ml/1.73 m2/min),5)  chronic  or acute  infection, 6)sepsis, 7) malignancy, 8) treatedwith  corticosteroid  or    nonsteroidal  anti  inflammatory  orimmunosuppresive  drugs morethan 1 weeks, and  9) stroke. Thisstudy using human MMP-9 ELISAkit  and Roche Elycsys  2010 kitwhich measured  48 hours  afteronset AMI.Analysis  of  correlationbetween MMP-9 with  hs-TnTusing  non-parametric  analysiswith  Spearman  test  (P<0.05).Multivariate  analysis  withmultiple  linear  regression  therelationship  of  the  functionalpredictive value MMP-9 and othersconfounding variable to plasma hs-TnT.  The  last  we  performedANCOVA analysis to determinethe  difference  of  strengthassociation between plasma MMP-9  and  hs-TnT  in  STEMI  orNSTEMI  group. Data  analysisusing SPSS  17 with  significantP<0.05.RESULTSA  total  of  62  samples wereincluded  in  this  study. Matrixmetalloproteinase-9  (MMP-9) andhs-TnT  plasma  levels  48  hoursafter AMI onset were measured.The samples also got  treatmentbased  on  ACS  guideline  fromPERKI 2014.12Subject characteristicsTotal 62 patients with AMIwere included, 50 males (80.6%)and 12 female (19.4%), with meanage 57.9 (SD 10.7) years. Thirtyfive patients were diagnosed withSTEMI  (56.5%) and 27 patientswith NSTEMI (43.5%) with meanonset between 6.74 (SD 3.8) hours.Cholesterol levels were between110-327 mg/dL, LDL levels werebetween 56.3-244.5 mg/dL, HDLkadar MMP-9  dengan hs-TnT  pada  penderita  IMA  dengan  kekuatan  korelasi  sedang  dan  secarastatistik signifikan (r= 0.507; Y= - 650.6 + 46.7(X1); P<0.0001); kadar MMP-9 plasma dan awitan IMAmempengaruhi kadar hs-TnT plasma pada penderita IMA dengan formula persamaan Y = - 815.0 +46.5(X1)+ 20.7(X2); (â MMP-9=46.5(IK 95% : 24.7 sampai 68,4); P<0.0001; â awitan IMA=20.7(IK 95%: 2.1 sampai 39.4); P=0.030).  dan kekuatan hubungan kadar MMP-9 dengan hs-TnT pada kelompokSTEMI lebih besar daripada NSTEMI. [MEDICINA 2015;46:22-27].
Keywords: MMP-9, hs-TnT, AMI, STEMI, NSTEMI